Linguagem escrita da Educação Infantil ao 1º ano do Ensino Fundamental: análise da transição segundo as professoras - Moraes, Keila Cristina Armando de (Universidade Federal de São Carlos, 2022)
The child establishes relationships with other human beings and with the environment from birth and expands their communication through different types of languages. Supported by the contributions of the Historical-Cultural Theory, this research aimed to investigate the teachers' perspective in conducting the transition process based on child development and the acquisition of written language, considering the symbolic function that is so important in the complex process of historical development. and cultural impact of written language acquisition in preschool children. I also sought knowledge of how the process of formation of higher psychic functions occurs in child development. Through scholars such as Vygotsky , Luria and contemporary authors who focus on child development and the prehistory of writing in the light of this same foundation, I theoretically explored research on human development and the role of school in the child's evolution, thinking and language in the movement of reflection and its interrelations, the process of acquisition of oral and written language, ending with the word in the interaction between thought and language as a means of human communication. The investigation is methodologically supported by qualitative research, of an applied, descriptive and exploratory nature, with the use of field research. Data generation was performed in two stages. The first, with 11 teachers from the first year of Elementary School, selected the semi-structured interview, carried out in person and following the security protocols required in the Covid19 pandemic, but also by the technological support Google Meet, when face-to-face contact was not possible. The second stage, as a complement to the data, was given a questionnaire to three teachers who teach both in Early Childhood Education and in Elementary School, confronting perceptions about what is being researched. The data generated, both in the interviews and in the questionnaire, were analyzed and interpreted through tables and descriptive texts, based on the Content Analysis method (BARDIN, 2011) and the results show that playfulness and games are present in the planning of the activities. teachers, the articulation of theory with pedagogical action still does not happen effectively, the differentiated look at work with verbal and non-verbal language, and also, the investment in continued education, in the urgency of strategies to change perspectives and posture in the process of transition between the stages of basic education, in the adaptation of a new routine, involving the entire school team. The importance of the Common Curriculum as a guiding thread is evident, considering that teachers still signal literacy in Early Childhood Education and the contradictions of writing assessment in the face of the Historical-Cultural Theory. In addition, school education provides stimulating educational activities to promote the advancement of children's language, including written language.
Written language from kindergarten to the 1st year of elementary school: analysis of the transition according to the teachers
Keywords: Educação Infantil; Transição; 1º Ano do Ensino Fundamental; Linguagem Escrita; Child education; Transition; 1st Year of Elementary School; Written language; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO